Advanced exergoeconomic analysis of a gas engine heat pump (GEHP) for food drying processes. (February 2015) - Gungor, Aysegul; Tsatsaronis, George; Gunerhan, Huseyin; Hepbasli, Arif
Highlights: Comparison between conventional and advanced exergoconomic analyses for food drying. 74% of the total energy destruction can be avoided. The condenser has the highest improvement potential. Inefficiencies and options for improvement are identified for each component. Abstract: Exergetic and exergoeconomic analyses are often used to evaluate the performance of energy systems from the thermodynamic and economic points of view. While a conventional exergetic analysis can be used to recognize the sources of inefficiencies, the so-called advanced exergy-based analysis is convenient for identifying the real potential for thermodynamic improvements and the system component interactions by splitting the exergy destruction and the total operating cost within each component into endogenous/exogenous and unavoidable/avoidable parts. In this study for the first time an advanced exergoeconomic analysis is applied to a gas-engine-driven heat pump (GEHP) drying system used in food drying for evaluating its performance along with each component. The advanced exergoeconomic analysis shows that the unavoidable part of the exergy destruction cost rate within the components of the system is lower than the avoidable part. The most important components based on the total avoidable costs are drying ducts, the condenser and the expansion valve. The inefficiencies within the condenser could particularly be improved by structural improvements of the whole system and the remaining system components. Finally, it can be concluded that the internal design changes play a more essential role in determining the cost of each component.